A facile and eco-friendly strategy to prepare synthetic syntans for after-treatment of dyed nylon fabrics. (November 2017) - Guo, Baofu; Li, Dan; Li, Chao; Mao, Yahong; Zheng, Qingkang; Tan, Lin; Yan, Bin
Abstract: Directly dyed nylon 6, 6 fabrics usually demand recourse to an after-treatment of synthetic tannins (a.k.a. syntans) to improve the fastness of dyeings to water and perspiration. However, the synthesis of commercial syntans requires highly acidic conditions and results in a huge amount of acidic waste effluent after reaction, which has caused severe pollution to the environment. Herein, we report an eco-friendly and feasible strategy to prepare a syntan in one pot in excellent yield via the multicomponent reaction of bisphenol S, formaldehyde and sodium phenolsulfonate in aqueous solution using NaOH as catalyst at 100 °C. This strategy can easily obtain a competent syntan bath for after-treatment to the dyed fabrics by dilution and neutralization, while at the same time ensuring much reduced discharge of acidic effluent to the environment after reaction. Compared to current commercial syntans, this new syntan demonstrates a comparable and satisfactory fixing performance on the dyed fabrics in terms of the level of color fastness of the treated fabrics to washing, rubbing, seawater as well as acidic and basic perspiration.